Features of the financial and economic analysis of the motor transport enterprises’ activity - T. V. Konovalova; S. L. Nadiryan; S. V. Nenastin (Вестник СибАДИ)
The authors have considered the specifics of financial and economic analysis of the motor transport enterprises’ activity. The functional and value type can be considered as the most full and objective type of financial and economic analysis of motor transport activity. As researches show, at conducting financial and economic analysis using the theory of marginal utility, it is able to consider not only financial, but also social and economic results of the motor transport activities.